Tathwîru Waraqah al-‘Amali fi Tarqiyah Mahậrah al-Kitậbah li At-Thullậbi bil Madrasah al-Mutawashitah Nûruhl Ikhlậs Kutu Kampar Hulu Kampar Riau/تطوير ورقة العمل في ترقية مهارة الكتابة للطلاب بالمدرسة المتوسطة نور الإخلاص كوتو كمبار هولو كمبار رياو - aini, aysafitra; hidayat, hakmi; agustiar, agustiar; rusdi, rusdi; zulbaida, zulbaida; hakim, sri wahyuni (Al-Manar, 2024)
ABSTRACTAysa Fitra Aini, (2024): The Development of Student Worksheet (LKPD) to improve the Writing Skills of students MTs Nurul Ikhlas Tabing Koto Kampar Hulu Kampar Riau.This study aims to Development of Student Worksheet (LKPD) to improve the Writing Skills of student MTs Nurul Ikhlas Tabing Koto Kampar Hulu Kampar Riau. The formulation of the problem in this study is how The Development of Student Worksheet (LKPD) to improve the Writing Skills of student MTs Nurul Ikhlas Tabing Koto Kampar Hulu Kampar Riau. The research method used is R&D with the ADDIE model (Analysis, Design, Development, Application, and Evaluation). The population in the study was all Class VIII Students of MTs Nurul Ikhlas Tabing Koto Kampar Hulu Kampar Riau. Data collection is done by observation, questionnaire, and documentation. Meanwhile, to analyze the data, researchers used the formula p = f / n X 100. The results of the study are as follows: (1) Student Worksheet (LKPD) are valid with a percentage of 91% in terms of material, 77% in language and 90% in design. (2) Student Worksheet (LKPD) are effective for improving students' Writing Skills, this can result in t (calculation) being greater than t (table) at degree 1. This shows that the alternative hypothesis is accepted and the null hypothesis is rejected.Keywords: Development, Student Worksheet (LKPD) and Writing Skillsملخصعائشة فطرة عيني 2024: تطوير ورقة العمل الطلاب في ترقية مهارة الكتابة للطلاب بالمدرسة المتوسطة نور الإخلاص كوتو كمبار هولو كمبار رياوهدف هذا البحث لإيجاد تطوير ورقة العمل الطلاب في ترقية مهارة الكتابة للطلاب بالمدرسة المتوسطة نور الإخلاص كوتو كمبار هولو كمبار رياو. أسئلة البحث كيف تطوير ورقة العمل في ترقية مهارة الكتابة للطلاب بالمدرسة المتوسطة نور الإخلاص كوتو كمبار هولو كمبار رياو. طريقة البحث المستخدمة بحث وتطوير بنموذج ADDIE (التحليل والتصميم والتطوير والتطبيق والتقويم). مجتمع البحث لطلاب الصف الثامن بالمدرسة المتوسطة نور الإخلاص كوتو كمبار هولو كمبار رياو. الأدوات التي استخدمتها الباحثة لجمع البيانات هي الملاحظة والتوثيق. وكانت ناتج البحث كما يلي: (١) ورقة العمل الطلاب صالحة من ناحية المواد بنسبة ٩١٪ واللغة ٧٧٪ والتصميم ٩٠٪. (٢) ورقة العمل الطلاب فعالية لترقية مهارة الكتابة للطلاب. ويمكن معرفة ذلك من نتيجة تاء الحساب أكبر من تاء الجدول على درجة ١٪. وهذا يدل على أن الفرضية البديلة مقبولة الفرضية المبدئية مردودة.الكلمات المفتاحية : التطوير، ورقة العمل الطلاب، مهارة الكتابة